Stenting versus non-stenting before extracorporeal shock wave lithotripsy for proximal ureteric stones: A prospective interventional study - Pogula, Vedamurthy Reddy; Reddy, Sandeep; Galeti, Ershad Hussain; Rasool, Mustaq (Asian Journal of Medical Sciences, 2022)
Background: Extracorporeal shock wave lithotripsy (ESWL) has become the first-line treatment for stones in the upper urinary tract measuring <2cm. It is the minor invasive treatment for calculi of the upper urinary tract. Aims and Objectives: This study aims to identify the effect of the presence and absence of a ureteric stent on the outcome of ESWL in patients with proximal ureteric stones. Materials and Methods: This was a prospective cohort study done on 300 patients and wasdivided into two equal groups of 150 each. Group A patients were selected for ESWL with DJ stent, and Group B patients werefor ESWL without DJ stent. Non-contrast CT KUB was done as a functional study along with plainX-ray KUB and ultrasound before the intervention. All treatments were done with Direx Compact XL (electromagnetic generator) device as an outpatient procedure. Patients were followed up radiographically at 15 days, 1 month, 2 months, and in 3 months. Hematuria, steinstrasse, fever, ureteric colic, lower urinary tract symptoms (LUTS), stone clearance, number of ESWL sessions, and secondary procedures were recorded for each group. DJ stent was taken out when the stone disappeared or at the end of 3 months. Variables were compared with Chi-square test. Results: The overall stone-free rate at 3 months was 90.6% (272/300). Clearance after the first sitting, second sitting, and the third sitting wasnot significant between the two groups(P>0.05).There was no significant difference between the two groups in regard to clearance according to the size of the stones. A total of 9.3%(28/300) of patients did not have a successful outcome and were termed as ESWL failures. Post- ESWL complications were significant between the both groups in terms of hematuria and ureteric colic. All the ureteric colic patients had a stone size larger than 13 mm, P=0.0005, which was more in the non-stented (Group B) patients. Most of the lower urinary tract symptoms were seen in stented (Group A) patients, P<0.0001 significant between the two groups, and dysuria was also significant between the two groups with P=0.0033. Conclusion: Pre-ESWL ureteral stenting provides no additional benefit over no stent in situ, although ureteral stents are associated with more irritative symptoms.